Simplified design of building foundations - Ambrose, James E. (New York : Wiley, 1988)
A fast guide to solving common design problems in building foundations, now in a new edition. Includes new material on settlements, soil modification, pole foundations, braced excavations, waterfront foundations, and slope stabilization. Written for those without full training as structural or design engineers, covering all the basics, including soil mechanics, design of common foundation elements, and the relations between building and foundation design, all supported by extensive illustrations. Mathematics is kept to a minimum, being generally restricted to simple algebra, plane geometry, and plane trigonometry.
General Considerations in Foundation Design. -- Soil Properties and Foundation Behavior. -- Shallow Bearing Foundations. -- Deep Foundations. -- Horizontal Forces in Soils. -- Special Foundation Problems. -- Appendix A: Reinforced Concrete Design: Working Stress Method. -- Appendix B: Excerpts from the 1963 ACI Code. -- Appendix C: Building Code Requirements for Foundations. -- Study Aids. -- Answers to Selected Problems. -- Index. -- References. -- Glossary.
"A Wiley-Interscience publication."
engineering bookfair2015
Includes index.
Bibliography: p. 189.
Keywords: Foundations -- Design and construction